2012
DOI: 10.1002/jsfa.5902
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of carotenoids originating from algae

Abstract: Carotenoids are isoprenoid molecules which are synthesised de novo by photosynthetic plants, fungi and algae and are responsible for the orange, yellow and some red colours of various fruits and vegetables. Carotenoids are lipophilic compounds, some of which act as provitamins A. These compounds can be divided into xanthophylls and carotenes. Many macroalgae and microalgae are rich in carotenoids, where these compounds aid in the absorption of sunlight. Industrially, these carotenoids are used as food pigments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
170
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(181 citation statements)
references
References 86 publications
(169 reference statements)
6
170
0
5
Order By: Relevance
“…A high concentration of reactive oxygen species can give rise to numerous diseases. Consequently, antioxidants have an important role in the treatment of medical and cosmetology problems (Christaki et al 2012;Herman & Herman 2013). The present study is used DPPH and FRAP assays to establish the antioxidant properties of acetone extract from H. physodes.…”
Section: Discussionmentioning
confidence: 99%
“…A high concentration of reactive oxygen species can give rise to numerous diseases. Consequently, antioxidants have an important role in the treatment of medical and cosmetology problems (Christaki et al 2012;Herman & Herman 2013). The present study is used DPPH and FRAP assays to establish the antioxidant properties of acetone extract from H. physodes.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that the amino acid pattern of these microalgae could be comparable with or superior to that of other vegetable foods and feeds, and that they have a high nutrient digestibility (Spolaore et al, 2006;Plaza et al, 2009;Alvarenga et al, 2011). In addition, spirulina contains substances such as pigments (for example carotenoids such as β-carotene and zeaxanthin) (Maoka, 2011), phycobiliproteins (for example phycocyanin, which is unique in the cyanobacteria (Eriksen, 2008), vitamins (Becker, 1994), macro and micro mineral elements (Becker, 1994;Spolaore et al, 2006) and antioxidants (Christaki et al, 2013). These compounds reveal potential biological properties such as antimicrobial, antioxidant, anti-cancer and anti-inflammatory or act as immune enhancers and colorants (Freitas et al, 2012;Batista et al, 2013;Christaki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, spirulina contains substances such as pigments (for example carotenoids such as β-carotene and zeaxanthin) (Maoka, 2011), phycobiliproteins (for example phycocyanin, which is unique in the cyanobacteria (Eriksen, 2008), vitamins (Becker, 1994), macro and micro mineral elements (Becker, 1994;Spolaore et al, 2006) and antioxidants (Christaki et al, 2013). These compounds reveal potential biological properties such as antimicrobial, antioxidant, anti-cancer and anti-inflammatory or act as immune enhancers and colorants (Freitas et al, 2012;Batista et al, 2013;Christaki et al, 2013). However, the total amount of nutrients in spirulina could be greatly affected by available nutrients and environmental conditions during growth (Ciferri, 1983;Tonon et al, 2002;Tzovenis et al, 2003;Spolaore et al, 2006;Habib et al, 2008), by harvesting and drying techniques (Borowitzka, 1988;Spolaore et al, 2006;Alvarenga et al, 2011) and by methods of nutrient determination (Ciferri, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…In this project, the acetone and diethyl ether in both formulas were respectively the best solvent for S. trinodis, P. myrica and C. sinuosa species in the field of chlorophyll extraction. With all the above, these tests still need to be explored further in the future, because there is high demand for use of natural pigments of algae in food products, particularly dairy and beverages [1] as food additives and also in cosmetics.…”
Section: Discussionmentioning
confidence: 99%